Seasonality and trends of dry forest of Piaxtla-Elota-Quelite basin and protected area Meseta de Cacaxtla, Mexico - Berlanga-Robles, César Alejandro; Cervantes-Escobar, Aimée; Murúa Figueroa, Eunice (Instituto de Ecología, A.C., 2018)
The tropical dry forests are one of the most vulnerable and unprotected ecosystem in Mexico. Currently, only 30% of the original cover remains and 0.2% of it is under some form of protection status. In order to promote the conservation and management of these ecosystems, the objective of this study was to describe the seasonality and trends change of the forest canopy of the Piaxtla-Elota-Quelite basin and the Meseta de Cacaxtla Flora and Fauna Protection Area in Sinaloa State, in Northwest Mexico. A monthly time series from 2001 to 2016 of the Normalized Difference Vegetation Index of the satellite Modis Terra was decomposed with a Principal Component Analysis with two orientations. In the analyzed period, 99% of the variation of the forest canopy was due to a vegetative phenological cycle, in which the maximum vigor of the vegetation occurred in September; three and four months after the beginning of the rainy season. Likewise, deforestation or reforestation processes were not identified in the basin. The Meseta de Cacaxtla has fulfilled its function of protecting its forest, and its good state of conservation detected in the whole basin could be an incentive to extend the limits of the protected natural area and to increase the percentage of tropical dry forest under protection status in Sinaloa, which is currently 0.02%.